Transformasi Metodologi Pendidikan Isalam: Integrasi Nilai Klasik dan Inovasi Digital di Era Society 5.0 - Nurhaibi Nurhaibi (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
The Society 5.0 era demands the field of education to integrate high-level technology with profound human needs. This article aims to analyze the transformation of Islamic education methodology from classical approaches to digital innovation without losing its spiritual essence. The core problem addressed is the dichotomy between tradition and modernity, as well as the crisis of digital role modeling (digital qudwah) among educators. Using a library research method, this study evaluates the integration of classical values such as adab, talaqqi, and hiwar with technological innovations like Artificial Intelligence (AI) and Virtual Reality. The results show that such integration creates a